Eksplorasi Kandungan Klorofil pada beberapa Sayuran Hijau sebagai Alternatif Bahan Dasar Makanan Tambahan - Setiari, Nintya -; Nurchayati, Yulita - (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2009)
Chlorophyll is a plant pigment which recently have been popular as food supplement. The source ofchlorophyll consumed now are alfalfa’s leaves algae such as Spirulina and Chlorella.. Chlorophyll content find in allkinds of plant especially vegetables so that have potent to be source of chlorophyll. The aims of this research are toexplore alternative source of chlorophyll aside of Leguminosae, from vegetables such as sweet basil, spinach, waterspinach, cassava leaves, pegagan, and papaya’s leaves and to study the vegetables potent to be food supplement.The experiment has been conducted by extracting 0,1 g each leaves in 10 mL acetone 85%. The extract was filteredwith Whatman paper No. 1, thus record the absorbance by using spektrofotometer UV Vis. Statistical analysis wasused to analyze chlorophyll content is Analysis of Variance (ANOVA) with Randomized Complete Design (RCD) in95% significancy. If the ANOVA showed significantly different, the analysis were continued with Duncan’s test.The result showed that the highest content of chlorophyll-a, b, and total found in papaya’s leaves. However thelowest one was found in sweet basil. Papaya’s leave potential as food supplement.